CHOLESTEATOMA OF THE EXTERNAL AUDITORY CANAL - Viveros Díez, Patricia; Benito Orejas, Jose Ignacio; Fernández Rodríguez, Ana; Cifuentes Navas, Viviana Andrea; Ramírez Salas, Jesus Eduardo; Morais Pérez, Darío (Revista ORL, 2019)
Introduction: Cholesteatoma of the external auditory canal (CEAC) is a rare entity characterized by the invasion of squamous tissue in the auditory canal, usually posterior-inferior area, with bone erosion, which differentiates it from another similar process. , the "keratosis obturans". The scarcity of published cases of CEAC and the opportunity to have been able to follow it up, have been the reasons for this study. Material and methods: We conducted a prospective and observational study from the year 2000 to the present in 17 patients clinically diagnosed with CCAE and evaluated in an ORL service of a tertiary hospital. The variables collected were: - Sociodemographic data (age at diagnosis and gender) - Affective hearing, location and evolutionary stage - Symptomatology (otalgia, otorrhea, pruritus, subjective hypoacusia or facial weakness) - Treatment, years of follow-up and recurrence. Results: Of the 17 patients identified in these 19 years, 53% were women and 47% men, with a mean age at diagnosis of 58 years (range of 21 to 83 years). The most frequently affected side was the right side (11/17), as well as its postero-inferior location, which appears in 12 of the 17 patients. Most of them present otalgia, otorrhea and subjective hearing loss, being less common the pruritus (8/17) and exceptional facial weakness (2/17). The clinical form that we have seen the most is that of a patient who goes to the emergency room for otalgia and / or otorrhea. In 11 of the 17 cases, we opted for a conservative treatment based on oily lotions and frequent cleaning of the canal outpatiently, but in 6 of the patients, a surgical treatment was necessary, based on canaloplasty, with modified radical mastoidectomy in 3 of them. The longest follow-up was 17 years and curiously in this last year we have diagnosed 4 of the 17 patients, who still attend reviews. Regarding the etiology, we believe that in 7 patients the origin is primary or spontaneous and the remaining 9 could be secondary to different causes, which include post-radiotherapy (1/8), post-surgery (2/8), post-traumatism in carriers of hearing aids (2/8), or postinflammatory and duct stenosis (3/8) Conclusions: Although we do not know the genesis and pathogenic mechanisms responsible of CEAC formation and development, the inclusion of keratin between the epithelium and bone, with the participation of the periosteum, seems to be the trigger of this process. Its evolution is variable and more or less silent. The diagnosis is clinical and its extension determines the use of a local or surgical treatment, which is usually resolutive.